The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2147/cmar.s147324
|View full text |Cite
|
Sign up to set email alerts
|

Influential factors on radiotherapy efficacy and prognosis in patients with secondary lymph node metastasis after esophagectomy of thoracic esophageal squamous cell carcinoma

Abstract: BackgroundThe purpose of this study was to clarify whether pretreatment tumor burden-related index, including the gross tumor volume (GTV) of metastatic lymph nodes (VLN) and maximum diameter of metastatic lymph nodes (DLN), and inflammatory markers, consisting of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), are useful for assessing the therapeutic effects and prognosis with secondary lymph node metastasis (LNM) receiving chemoradiotherapy (CRT) or radiotherapy (RT) alone after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The clinical features of the patients, such as age, ECOG PS, metastatic sites, treatment line, drug differences and so on, may be also associated with the treatment response and prognosis. Our results indicated that patients with lymph node metastasis negative had significantly better survival than those with lymph node metastasis positive, which supported the previous findings that lymph node metastasis was a worse prognostic indicator in EC patients accepting surgery ( 39 , 40 ), radiotherapy or radiochemotherapy ( 41 ). Notably, previous studies demonstrated that patients with liver metastases were insensitive to immunotherapy in various cancers such as melanoma ( 42 ), NSCLC ( 43 ), and urothelial carcinoma ( 44 , 45 ).…”
Section: Discussionsupporting
confidence: 91%
“…The clinical features of the patients, such as age, ECOG PS, metastatic sites, treatment line, drug differences and so on, may be also associated with the treatment response and prognosis. Our results indicated that patients with lymph node metastasis negative had significantly better survival than those with lymph node metastasis positive, which supported the previous findings that lymph node metastasis was a worse prognostic indicator in EC patients accepting surgery ( 39 , 40 ), radiotherapy or radiochemotherapy ( 41 ). Notably, previous studies demonstrated that patients with liver metastases were insensitive to immunotherapy in various cancers such as melanoma ( 42 ), NSCLC ( 43 ), and urothelial carcinoma ( 44 , 45 ).…”
Section: Discussionsupporting
confidence: 91%
“…Combining chemotherapy (e.g. cisplatin, 5-fluorouracil, and paclitaxel) with targeted inhibitors can potentially overcome radioresistance and extend progression-free and overall survival (7)(8)(9)(10)(11)(12). However, few studies have examined the efficacy of combined treatments in preventing distant metastasis (10).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou's team found that the maximum diameter of metastatic lymph nodes may be an effective biomarker to predict the prognosis of patients who received radiotherapy after esophagectomy ( 19 ). Wu's team believed that the AUC for the minimum diameter of lymph nodes and the maximum diameter of lymph nodes for diagnosing lymph node metastasis were 0.679 and 0.666, respectively.…”
Section: Discussionmentioning
confidence: 99%